Integrating metacognitive and psychometric decision-making approaches for bank customer loyalty measurement - Jalali, M. S. (2017)
Greater competition and the aftermath of the financial crisis have meant that banks are increasingly focused on improving service quality and achieving higher levels of customer loyalty. Doing so requires being able to identify, understand and measure the determinants of such loyalty, however; and given the variety of multi-faceted factors involved, and the interrelationships among them, this is a complex undertaking. This paper proposes and tests an integrated application of cognitive mapping and multiple criteria decision analysis (MCDA), thus combining metacognitive and psychometric decision-making approaches, to create a framework for the assessment of bank customer loyalty, which identifies its determinants and allows the trade-offs among them to be calculated. Practical advantages and limitations of our proposal are also discussed.